2019
DOI: 10.3934/dcdsb.2018288
|View full text |Cite
|
Sign up to set email alerts
|

Convex geometry of the carrying simplex for the May-Leonard map

Abstract: We study the convex geometry of certain invariant manifolds, known as carrying simplices, for 3-species competitive Kolmogorov-type maps. We show that if all planes whose normal bundles are contained in a fixed closed and solid convex cone are rendered convex (concave) surfaces by the map, then, if there is a carrying simplex, it is a convex (concave) surface. We apply our results to the May-Leonard map.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…Repeating the above process we obtain x k (n) < 2 3 y k for all n ≥ m 1 , a contradiction to y ∈ ω(x). The contradictions in both cases above show that ω(x) ⊂ (∩ k ℓ=1 π ℓ ) ∩ Σ.…”
Section: (A) Under the Assumption Thatmentioning
confidence: 91%
“…Repeating the above process we obtain x k (n) < 2 3 y k for all n ≥ m 1 , a contradiction to y ∈ ω(x). The contradictions in both cases above show that ω(x) ⊂ (∩ k ℓ=1 π ℓ ) ∩ Σ.…”
Section: (A) Under the Assumption Thatmentioning
confidence: 91%
“…Some progress has been made here for continuous time competitive Lotka-Volterra systems by Zeeman and Zeeman [40]. Recent progress on the convexity or concavity of carrying simplices for competitive maps can be found in [5,3]. • a bifurcation analysis that links change in stability to change in geometry of the carrying simplex local to a fixed point.…”
Section: Discussionmentioning
confidence: 99%
“…Baigent [5] studied the existence of the planar Leslie-Gower model under similar conditions, and also showed that the carrying simplex was either a convex or concave curve. Recently, Baigent studied the 3-dimensional Leslie-Gower model [3] in May-Leonard form and established parameter regions where the carrying simplex was either convex or concave.…”
Section: The Leslie-gower Modelmentioning
confidence: 99%
“…Mierczyński proved in [21,22] that the carrying simplex is a C 1 submanifold-with-corners neatly embedded in the nonnegative orthant when it is convex. For the convexity of the carrying simplex and their influence on the global dynamics, we refer the reader to [23,24,8,25,26]. Whether the carrying simplex is smooth or not is still unknown when it is not convex.…”
Section: Introductionmentioning
confidence: 99%